2021
DOI: 10.3390/app11209720
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Methylene Blue Dye by Electrospun Binary and Ternary Zinc and Titanium Oxide Nanofibers

Abstract: Synthetic dyes, dispersed in water, have harmful effects on human health and the environment. In this work, Ti and/or Zn oxide nanofibers (NFs) with engineered architecture and surface were produced via electrospinning followed by calcination. Calcination and subsequent cooling were operated at fast rates to generate porous NFs with capture centers to reduce the recombination rate of the photogenerated charges. After morphological and microstructural characterisation, the NFs were comparatively evaluated as ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…The size of particles was 18.9 nm. After 40.2 minutes, the rate of decomposition was 81.7% [27]. MB dye has been tested with THNF-400 (Titanium Dioxide hollownanofibre).…”
Section: Photocatalytic Activity Of Tio2 Npsmentioning
confidence: 99%
“…The size of particles was 18.9 nm. After 40.2 minutes, the rate of decomposition was 81.7% [27]. MB dye has been tested with THNF-400 (Titanium Dioxide hollownanofibre).…”
Section: Photocatalytic Activity Of Tio2 Npsmentioning
confidence: 99%
“…That is, the presence of adjacent Ti vacancies stabilizes the oxygen vacancies [29]. S.S. Al-Shamali [30] reported photodegradation rate of 90% of MB dye in TiO2 photocatalyst with pH values ranging from 4 to 8. A comparable study was undertaken by a number of other researchers, as shown in Table 2.…”
Section: Photodegradation Of Mb Dyementioning
confidence: 99%
“…The report did not rationalize the effect of the pH value. Other reports have described ZnTiO 3 nanopowders and nanofibers in the photodegradation of methylene blue with no reference to the pH effect [18,55]. In another report [56], ZnTiO 3 supported on clays and zeolites adsorbed more methylene at higher pH values within the range of 2-10.…”
mentioning
confidence: 94%